Wicked Dreams - Jackson, Lisa; Bush, Nancy, 1953- (Thorndike, Maine : Center Point Large Print, 2023)
"The note pinned to the dead body found on the remote beach has no name, just Ravinia Rutledges phone number and the words "Next of Kin." Ravinia insists she doesnt recognize the man on the mortuary slab, but she suspects Detective Nev Rhodes doesnt believe her. He can tell that shes one of them - the Siren Song women. Five years after moving away from The Colony, Ravinia has carved out a life as a private investigator whose specialty is helping others locate their missing loved ones. Yet sometimes, its better if the missing are never found. "Good Time Charlie" is the name given to a monster from her past, a man whom she and her sisters hoped was gone forever. But the dead man on the beach is a sign that Charlie has merely been waiting, preparing to fulfill his mission to rid the world of the Siren Song women - and anyone else who gets in his way. Rhodes has his own reasons for being fascinated with The Colony and its surroundings - a place marked by unexplained deaths and tragedies. Rhodes plays by the rules, but there are forces at work here that defy notions of law and order. And despite Ravinias reluctance to team up with Nev, its the only way to stop an adversary determined to see that each and every member of The Colony will die at his hands. . . "--
Keywords: Private investigators -- Fiction; Ex-cultists -- Fiction; Cults -- Fiction; Murder -- Fiction; Secrecy -- Fiction; Oregon -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Large print books